ปรสิตการสื่อสารในรายการโทรทัศน์เล่าข่าวเช้า - ริรินดา เติมไทยมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This qualitative research is focused on "Communication Parasite" in television s morning news talk shows, and how they transmit subliminal messages to the shows audience. Results indicate that Communication parasite in television morning news talk can be classified in 4 levels as follows: 1. Communication parasite within Television Media. 2. Communication parasite within Television Station. 3. Communication parasite within Television Program. 4. Communication parasite within Text. The subliminal messages of communication parasite in television’s morning news talk shows may be varied as a result of several factors i.e. television networks, which are the channels policy-setter, the condition from the producers of the shows on the necessity of the communication parasites to the show, the conditions from the sponsors on how they want their logos and products to be placed, the demand of the audience, the government, a very influential factor to the network, who can ask cooperation regarding the presentation of the shows from the networks at anytime. Also, the research found that, because of the mobility characteristic of the television media, the status of the communication parasites can be altered whenever the show format is changed.